Assessment of the influence of the level of mineral nutrition on the morphological parameters and accumulation of biogenous elements in the biomass of the fast-growing willoow - Butsko, Andrei A.; Rodzkin, Aleh I.; Rakovich, Viacheslav A.; Markitantov, Nikolaj R. (Journal of the Belarusian State University. Ecology, 2022)
The article presents the results of studies for assessment of the influence of the level of mineral nutrition on the morphological parameters and accumulation of biogenic elements in the biomass of the fast-growing willow Salix alba, cv. Volmyanka. A vegetation experiment to study the dependence of the morphological parameters of willow and the accumulation of nitrogen and phosphorus in the biomass of plants on the level of mineral nutrition have been done at the experimental site (53°55’24.6 “N,27°40’04.7” E) of the Institute of Research institute of nature management Academy of science of Belarus. The vegetation experiment was based on the following options: control, without additional application of mineral fertilizers; option N50P50 (dose of application 0.5 g per vessel); option N100P100 (the dose of application is 3.0 g per vessel); option N150P150 (dose of application 4.5 g). In the vegetation experiments, the dependences of the content of total nitrogen (Ntot) and Р2О5 in the biomass of a willow plant from the doses of mineral fertilizers and the content of mineral nitrogen Nmin) and Р2О5 in the soil were obtained. The influence of the content of Nmin (N-O3 + NH4) in the soil on the content of Ntot in the plant biomass is expressed by a high degree of quantitative and qualitative characteristics of the correlation (R2 = 0.778). The influence of the content of mobile phosphorus in the soil (from 200 to 600 mg/kg) on the content of Р2О5 in the plant biomass is expressed by a moderate quantitative and qualitative characteristic of the correlation (R2 = 0.403); (from 600 to 900 mg/kg) - very high (R2 = 0.928). The influence of mineral fertilizers on the content of Р2О5 and Ntot in the aboveground plant biomass during the growing season has been established. The influence of the doses of mineral fertilizers on the productivity and morphological parameters of the aboveground biomass of willow plants has been determined. The research results confirm the assumption about the possibility of using the plantation of fast-growing willow (Salix alba), cv. Volmyanka, as a vegetative filter capable to accumulate nitrogen and phosphorus in the plant biomass, preventing their penetration into water bodies and reducing the risk of eutrophication.
Keywords: nutrients; nitrogen; phosphorus; fast-growing willow; cultivar Volmyanka; Salix alba; productivity; growth rate